The Evolution of Political Violence: The Case of Somalia's Al-Shabaab. Issue 1 (2nd January 2018) - Mueller, Jason C.
ABSTRACT: This research investigates the development and expansion of the al-Shabaab movement in Somalia from 2000 to 2013. Initially a marginal player in Somalia, by 2013 al-Shabaab had transformed into the most formidable armed opposition to challenge the nascent Somali government and its allies. During this time period they administered territory domestically, while expanding their tactical repertoire and geographic scope of attacks. After analyzing the historical conditions (2000–2006) from which al-Shabaab emerged, I explore the evolution of this organization through the use of historical process tracing. This entails looking for critical junctures on a global, national, and local level that had a dramatic impact on the future trajectory of the insurgency. The results show that harsh foreign interventions had many deleterious consequences, acting as an initial impetus for armed resistance, while also acting as a continuous source of controversy which al-Shabaab exploited to gain new recruits. Moreover, irreconcilable intra-organizational schisms also contributed to altering the future organizational decisions made by al-Shabaab. The culmination of these results engage and expand the theory of categorical terrorism, offering observations to help scholars and policy makers alike begin to re-conceptualize ways to study terrorism and political violence.